2019
DOI: 10.5713/ajas.18.0543
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactic acid bacteria and molasses on fermentation dynamics, structural and nonstructural carbohydrate composition and in vitro ruminal fermentation of rice straw silage

Abstract: Objective This study was to evaluate the fermentation dynamics, structural and nonstructural carbohydrate composition and in vitro gas production of rice straw ensiled with lactic acid bacteria and molasses. Methods Fresh rice straw was ensiled in 1-L laboratory silos with no additive control (C), Lactobacillus plantarum (L), molasses (M) and molasses+ Lactobacillus plantarum (ML) for 6, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 22 publications
8
34
0
Order By: Relevance
“…However, cellulase or cellulolytic enzymes or bacteria could promote the degradation of crude fiber to dietary degradable carbohydrates such as glucose and organic acid (Tamboli et al, 2017). Therefore, RSSA supplementation enhanced the nutrients digestibility, and similar to this in vivo study, the application of bacterial inoculant also increased nutrients digestibility of rice straw silage in vitro (Zhao et al, 2019). Thereby, ruminal microorganisms can easily degrade the carbohydrate to produce volatile fatty acids, which promote the nutrient digestibility.…”
Section: Resultssupporting
confidence: 64%
“…However, cellulase or cellulolytic enzymes or bacteria could promote the degradation of crude fiber to dietary degradable carbohydrates such as glucose and organic acid (Tamboli et al, 2017). Therefore, RSSA supplementation enhanced the nutrients digestibility, and similar to this in vivo study, the application of bacterial inoculant also increased nutrients digestibility of rice straw silage in vitro (Zhao et al, 2019). Thereby, ruminal microorganisms can easily degrade the carbohydrate to produce volatile fatty acids, which promote the nutrient digestibility.…”
Section: Resultssupporting
confidence: 64%
“…In support, Huisden et al [19] reported that the addition of molasses to corn silage supplied an extra source of WSC for LAB metabolism, which possibly allowed their domination in the microbial community of the silage, thereby stimulating favorable silage fermentation patterns. Earlier findings confirmed that the combined use of the LAB inoculant and molasses improved the silage quality indices of various crops [7,8,22]. For example, our recent investigation [8] found that the combination of LAB and 5% molasses efficiently improved the silage quality parameters of spent mushroom substrate in both laboratory-scale and ton-bag silos.…”
Section: Silage Fermentation Quality Of Garlic Stalksupporting
confidence: 71%
“…It cannot be neglected that most straw is ensiled with high fermentation losses even if the fermentation accelerant is added. In our previous study [2], high ammonia nitrogen (NH 3 -N) and ethanol content were produced not only in control but also in rice straw en-siled with molasses or enzyme and lactic acid bacteria (LAB). Considering the relatively low protein and water soluble carbohydrates (WSC) content in rice straw, it seems particularly important to reduce protein and substrate losses during ensiling.…”
Section: Introductionmentioning
confidence: 99%